The urban lighting in the rehabilitation of the minor historical centre. The design scenarios for the architectural valorisation and the energy efficiency improvement of the urban environment - Pierluigi De Berardinis; Chiara Marchionni; Luisa Capannolo (Vitruvio: International Journal of Architectural Technology and Sustainability)
In the last decades, the topic of lighting of the historical minor centres is taking a prominent role in the cultural debate on the urban recovery interventions, because of the development of a greater awareness of the regenerative potential role that a careful planning system of urban lighting can take in this context.